Injuries in judo: Comparison of the risk profile in Japan, Germany, and USA - Ozawa, Y.; Abe, J.; Oku, Y.; Ganshow, R. (Association for the Scientific Studies on Judo, Kodokan, 2013)
Judo, meaning "gentle way", is a modern Japanese martial art and combat sport, which originated in Japan in the late nineteenth century. Its most prominent feature is its competitive element, where the object is either to throw one's opponent to the ground, immobilize, or otherwise subdue one's opponent with a grappling maneuver or to force an opponent to submit by joint locking the elbow or by applying a choke. Judo has its roots in Jujitsu, which was the martial art of the Samurai. The founder of Judo, Jigoro Kano, removed most life-threatening and potentially dangerous techniques and formed a martial art form that could be trained without injuring the partner. The main principle is to achieve most eff ect by least eff ort. Judo spread quickly to Europe and has gained popularity worldwide. As of 2012 about 200 countries are members of International Judo Federation. Since 1964 for men and since 1992 for women Judo is offi cially an Olympic sport (2). Japanese training and combat style are considered as the traditional way of Judo, whereas other countries have influenced the international competition sport of Judo and also developed other training philosophies and different styles in the internationalization process. These differences could cause diff erent risk profi les in Japan and in other countries. Reports on injuries in Judo are scarce and often restricted to a small group of athletes (3 . 11). To our knowledge there is no survey comparing injuries in judo by country on an extended scale. The objective of this study is (a) to elucidate the injury and training profile of judo athletes in different countries, and (b) to compare these results in order to provide a basis for injury prevention.